2009
DOI: 10.1111/j.1742-7843.2008.00302.x
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin and Indomethacin Have Similar Anti‐Inflammatory Activity in a Rat Model of Acute Local Inflammation

Abstract: Statins, such as simvastatin, lower circulating cholesterol levels and are widely prescribed for the treatment of hypercholesterolaemia. Several studies have shown unexpected effects of statins on inflammation. We studied the anti-inflammatory effect of simvastatin using a standard model of an acute local inflammation, the carrageenan-induced footpad oedema. Experimental groups (n = 6 -8) were given simvastatin in a dose range 5-30 mg/kg, indomethacin 1-8 mg/kg and methylcellulose (control) per os . Footpad vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…These findings were consistent with, and may partially explain, the preservation of interproximal bone volume and bone thickness in the SIM–ALN–CD/LPS group. These results were not unexpected because simvastatin previously has been shown to reduce inflammation and osteoclast numbers in rats. Alendronate has long been known to inhibit osteoclast activity in rats ; however, local alendronate may have little effect on osteoclast numbers and inflammation .…”
Section: Discussionsupporting
confidence: 61%
“…These findings were consistent with, and may partially explain, the preservation of interproximal bone volume and bone thickness in the SIM–ALN–CD/LPS group. These results were not unexpected because simvastatin previously has been shown to reduce inflammation and osteoclast numbers in rats. Alendronate has long been known to inhibit osteoclast activity in rats ; however, local alendronate may have little effect on osteoclast numbers and inflammation .…”
Section: Discussionsupporting
confidence: 61%
“…Prevalent hemodialysis patients under statins treatment presented significantly reduced MPO activity 35 . Nezić et al 36 observed that, at a dose range of 5 to 30 mg/kg, simvastatin reduced polymorphonuclear leukocyte infiltration in the carrageenan‐induced footpad edema model, dose dependently and comparably to indomethacin.…”
Section: Discussionmentioning
confidence: 99%
“…(0.25 LD 50 /kg). This experimental sepsis is a widely accepted model that is featured with high-grade acute systemic inflammation, inflammatory infiltration, increased oxidative stress, and apoptosis of organ tissues [ 14 , 38 , 39 ]. Simvastatin was administered in the three different dose regimens (10, 20, and 40 mg/kg p.o.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous experimental studies demonstrated that statins, well-known lipid-lowering drugs, improved survival, and prevent tissue and organ injuries in local inflammation [ 14 ] or sepsis induced by LPS or CLP [ 15 , 16 ]. By inhibition of hydroxy-3-methylglutaryl-CoA (HMG-CoA), reductase statins block the mevalonate pathway and activation of intermediate products involved in cell signaling pathways, such as apoptosis or cell survival.…”
Section: Introductionmentioning
confidence: 99%